Method for surface modification and densification of low bulk density materials - Patents.com

JP2025506950APending Publication Date: 2025-03-13ARKEMA INC
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2024552104
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2022-03-02
Filing Date
2023-01-31
Publication Date
2025-03-13

Smart Images

  • Figure 2025506950000001
    Figure 2025506950000001
Patent Text Reader

Abstract

A method is provided for increasing the bulk density of a low bulk density material by gently mixing the low bulk density material with a liquid, followed by removing substantially all of the liquid, for example by evaporation.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for surface modifying and densifying low bulk density materials such as fumed silica (i.e., pyrogenic silica), and more particularly to a method for increasing the bulk density of fumed silica by contacting the fumed silica with a suitable liquid under mild blending conditions and then evaporating the liquid to obtain a higher density fumed silica material. [Background technology]

[0002] Fumed silica is a well-known reinforcing agent or filler that is commonly used to improve the physical properties of various materials. There is an increasing demand for fumed silica in many applications, such as those related to silicone elastomers, adhesives, sealants, and unsaturated polyester resins (UPRs). UPRs are widely used to manufacture fiber-reinforced plastics in building structures, pipes, tanks, and automotive applications. They also find applications in fuel storage tanks, cooling tower components, beams, rudder rails, boat hulls, decks, and small automotive parts (both interior and exterior). Fumed silica is suitable for use in reinforcing silicone rubbers, such as heat-cured rubbers, high-temperature vulcanized silicone rubbers, and liquid silicone rubbers, and can increase their hardness, tensile strength, and elongation.

[0003] Fumed silica is also used as a multifunctional additive in the pharmaceutical and nutraceutical industries. Its glidant and antistatic properties help improve powder flow and reduce friction and static charge in high-speed tablet presses and encapsulation machines. Fumed silica adheres easily to hydrophilic ingredients and acts as an excellent glidant. It is also used as a tablet disintegrant, filler, lubricant, binder, and adsorbent in tablets, capsules, and powders. Fumed silica is also used in liquids, creams, and suspensions. It is also suitable as an anticaking agent because it absorbs water from the surface of particulate matter.

[0004] Fumed silica contains extremely finely divided silicon dioxide particles in the form of a powder, the specific surface area of ​​which typically ranges from about 100 to about 400 square meters per gram.

[0005] A major drawback of such low bulk density materials is that they are light-weight and have a fluffy powder structure, resulting in high transportation and storage costs. Compounders or formulators, for example, who require large quantities of such fillers must pay extra for transportation because shipping containers, such as railroad cars, cannot accommodate large quantities by weight. Furthermore, once a compounder or formulator receives such fillers, he or she must also pay for suitable storage areas, such as warehouses, silos, and the like. It would therefore be highly desirable to have a means for increasing the bulk density of such low bulk density materials in order to reduce transportation and storage costs.

[0006] Mechanical means do exist by which the bulk density of fine powder materials such as fumed silica can be increased. For example, U.S. Pat. No. 3,114,930 (Oldham et al.) uses a vacuum to remove air from air-containing fine powder materials, thereby reducing density. U.S. Pat. No. 3,664,385 (Carter) uses a rotating screw feeder to compact finely divided particulate materials. U.S. Pat. No. 4,325,686 (Leon et al.) obtains densification by employing a pair of opposed gas-permeable belts aligned on opposite sides of a common axis, thereby establishing densification zones between their adjacent faces that are generally close together.

[0007] Although the bulk density of many materials can be increased by mechanical means, certain difficulties and disadvantages remain. For example, in the case of fumed silica, increasing the density by mechanical devices to greater than about 6 pounds per cubic foot produces unacceptably large amounts of agglomerates and grit. Furthermore, it has also been found that fumed silica densified by mechanical means no longer disperses as well as the original fumed silica of lower bulk density.

[0008] U.S. Patent No. 4,780,108 (Razzano) discloses a non-mechanical method of increasing the bulk density of a low density bulk material by vigorously mixing the low bulk density material with an organic or organopolysiloxane liquid and then removing the organic or organopolysiloxane liquid. Razzano further discloses that such silicas no longer disperse in silicone compositions as well as the original silica of lower bulk density.

[0009] U.S. Pat. No. 4,898,898 (Fitzgerald et al.) provides a method for blending fumed silica or other finely divided materials with silicone polymers, thereby obtaining free-flowing powders having higher densities than can be obtained by mechanical means. Summary of the Invention

[0010] Surprisingly, the inventors have found that adding an aqueous liquid, such as water or water containing soluble compounds (such as hydrogen peroxide, acids, bases, alcohols, esters, ketones, salts, soluble polymers, etc.), by dripping or spraying with gentle agitation to a low density fine powder material, such as fumed silica, followed by evaporation of such liquid, results in a substantial increase in the bulk density of the fine powder material. The material is densified while retaining the homogeneity of the powder morphology of the low bulk density material, i.e., without unacceptably large amounts of agglomerates and grit. The method of the present invention provides a densified material that exhibits properties substantially equivalent to the original low bulk density material.

[0011] One object of the present invention is to provide a method for increasing the bulk density of a low bulk density fumed silica material without altering its absorbency or dispersibility.

[0012] It is yet another object of the present invention to provide a method for increasing the bulk density of a low bulk density material while retaining its homogeneity in powder form, i.e., without the formation of unacceptably large amounts of agglomerates and grit.

[0013] In the present invention, a method is provided for increasing the bulk density of a low bulk density fumed silica material, which comprises the steps of: (A) adding an aqueous, preferably polar, liquid to a low bulk density, preferably fumed silica material via a drip or spray method; (B) gently mixing the low bulk density material and the aqueous liquid for a time effective to reduce the volume of the original low bulk density material while preserving the homogeneity of the low bulk density material; and (C) removing substantially all of said aqueous liquid to obtain a material having an increased bulk density.

[0014] In a particularly preferred embodiment, the low bulk density material is fumed silica and the aqueous liquid is water or water containing soluble compounds such as hydrogen peroxide, acids, bases, alcohols, esters, ketones, salts, soluble polymers, etc. The water soluble compounds may further include surfactants, enzymes, etc. suitable for cleaning the reaction products. The water soluble compounds may further include colorants, fragrances, etc. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0015] The present invention provides a method for increasing the bulk density of a low bulk density material, which comprises the steps of: (A) adding an aqueous, preferably polar, liquid to a low bulk density fumed silica material via a drip or spray method; (B) gently mixing the low bulk density material and the aqueous liquid for a time effective to reduce the volume of the original low bulk density material while preserving the homogeneity of the low bulk density material; and (C) removing substantially all of said aqueous liquid to obtain a material having an increased bulk density.

[0016] In general, the low bulk density material may be any of a variety of compositions that may generally be classified as a "powder." For purposes of this invention, a powder is defined as any of a variety of solid, dry materials of extremely small particle size, ranging down to colloidal size, prepared either by comminution (mechanical grinding) of larger building blocks, by combustion processes (e.g., fumed silica), or by precipitation from a chemical reaction.

[0017] An example of a powder that can be employed in the practice of the present invention is fumed silica, which can be either hydrophilic or hydrophobic (treated).

[0018] Of particular interest is fumed silica, which is the most preferred low bulk density material for use in the practice of the invention. For convenience, hereinafter the terms "fumed silica", "low bulk density material" and "low bulk density fumed silica" will be understood to include the various materials that fall within the definition of powder given above.

[0019] The aqueous liquid that can be mixed with the low bulk density material described above to produce the advantageous results of the present invention can be polar or non-polar. In the case of treated silica (i.e., hydrophobic silica), a non-polar liquid will be required to wet the reaction product. In the case of untreated silica (i.e., hydrophilic silica), a polar liquid will be preferred. The polarity range of the liquid can be varied based on the hydrophobic / hydrophilic ratio of the silica material. Preferred aqueous liquids are polar liquids such as water or water containing soluble compounds such as hydrogen peroxide, acids, bases, alcohols, esters, ketones, salts, soluble polymers, etc. Preferred aqueous liquids may further contain surfactants, enzymes, etc. suitable for cleaning the reaction product. The most preferred aqueous liquid is an aqueous solution of water and hydrogen peroxide. There is no limitation on the concentration of the aqueous hydrogen peroxide solution in the present invention. The hydrogen peroxide concentration is preferably in the range of 0.1% to 70% hydrogen peroxide, more preferably 35% to 70%.

[0020] As those skilled in the art will appreciate, many other powders and aqueous liquids than those specifically described herein may be used to practice the present invention without departing from the intended scope of the appended claims.

[0021] In the practice of the invention, the low bulk density fumed silica material is placed in a suitable mixing vessel. An aqueous liquid effective to densify the low bulk density fumed silica material is added by dripping or spraying onto the fumed silica, followed by gentle mixing to homogenize. The addition of the liquid is preferably done with stirring, which provides good homogenization and avoids wet spots that lead to the formation of agglomerates. However, it is within the scope of the invention to use minimal stirring followed by more vigorous blending. The addition of the liquid is preferably followed by a period of mixing to homogenize (to break up wet spots and weak agglomerates). The duration and intensity of the mixing will vary depending on the batch size and the amount of liquid added. The application of the aqueous liquid and gentle mixing can be done in a series of successive steps, including repeated steps of adding the aqueous liquid and gentle mixing until the desired reduction in the volume of the low bulk density fumed silica material is achieved. The material is then dried to remove the aqueous liquid.

[0022] The inventors have discovered that the gentle mixing of the low bulk density material with an aqueous liquid results in a homogenous material, i.e., substantially free of agglomerates and coarse particles, similar to the original powdered material, which substantially fully retains the absorbent properties of the original low bulk density material, but with minimal or no agglomerate and coarse particle formation. The resulting homogenous material is a volume-reduced, densified material that is powdery, free-flowing, and substantially free of agglomerates and / or coarse particles.

[0023] The term "effective amount of aqueous liquid" refers to an amount of aqueous liquid sufficient to reduce the volume of the original low bulk density fumed silica material to a desired level. The magnitude of the effective amount of liquid will vary depending on the low bulk density fumed silica material employed, the aqueous liquid employed, and the volume / density change desired. Those skilled in the art will be able to determine such amounts without undue experimentation. As a general guideline, the minimum amount of aqueous liquid that can be employed must be sufficient to "wet" the particulate matter of the low bulk density material, i.e., to contact substantially all of it, thereby causing a volume reduction of the low bulk density material with gentle mixing. The maximum amount of liquid desired is an amount sufficient to indicate the presence of excess liquid after mixing. However, there is no upper limit, since the liquid is removed, for example, by evaporation methods, after gentle mixing of the low bulk density material with the aqueous liquid is complete. The amount of liquid required will vary depending on the specifications (e.g., surface area) of the fumed silica and the type of liquid (e.g., polarity). Polar and non-polar liquids can be employed. Non-limiting examples of polar liquids include water, acetone, and 1-butanol. Non-limiting examples of non-polar liquids include benzene, n-hexane, and carbon tetrachloride.

[0024] Other parameters, such as the intensity of mixing, can affect the densification process as well. In the present invention, such mixing should be gentle in order to avoid excessive densification, which leads to a wet-looking, inoperable saturated material. The reaction product thus obtained should not be saturated in appearance, but should have some coherence, yet still be flowable in the blend after the liquid is added. It is believed that too much shear caused by vigorous mixing can alter the physical structure or agglomerates of the fumed silica. This, in turn, can greatly alter the overall performance of the final product.

[0025] Particularly preferred for mixtures of fumed silica and aqueous hydrogen peroxide should be at least about 15% by weight, more preferably at least about 60% by weight, of aqueous hydrogen peroxide based on the weight of the fumed silica. As can be inferred from the examples referred to hereinafter, the effective amount of liquid should be as much as three times as much as the fumed silica by weight.

[0026] The mixing of the low bulk density fumed silica material with the aqueous liquid is preferably carried out in a mixing vessel that provides gentle agitation, such as a mixer or blender that is operated intermittently, i.e., for short periods of time, so that substantially all of the particulate material is wetted by the liquid. However, for purposes of the present invention, the terms "mixing vessel" or "mixing in a suitable vessel" and other equivalent terms are intended to include any means that is effective to wet the low bulk density material with the liquid. For example, rolling, spraying, fluidizing, and stirring are all acceptable. Agitation and powder blending can be achieved by, but is not limited to, ribbon blenders, paddle blenders, and equivalents, provided that the agitation / mixing is gentle and not vigorous. As will be appreciated by those skilled in the art, the process of the present invention can be carried out in either a batch or continuous manner.

[0027] The time required to impart mixing must be sufficient to reduce the volume of the original low bulk density material. Thus, the mixing time can vary from as little as 5 or 10 seconds to as little as an hour or more. Of course, the mixing time will depend on the particular low bulk density material, the liquid used in the practice of the invention, the intensity of the mixing, and the amount of liquid employed. One of ordinary skill will be able to determine effective mixing times without undue experimentation.

[0028] If after gentle mixing the volume of the original low bulk density material does not change substantially, further densification can be achieved by adding additional liquid and continuing gentle mixing for a second period of time. Such a process can be repeated until the desired reduction in the volume of the low bulk density material is achieved.

[0029] Moreover, in some cases it may be advantageous to proceed in a stepwise manner and then remove the liquid by evaporative techniques. As can be readily appreciated, the less liquid present, the less energy will be required to evaporate it.

[0030] The ratio between the silica and the liquid will vary depending on the properties of the silica and the liquid. For example, a 30 / 70 (silica / liquid) ratio may be appropriate. However, the ratio will vary if the silica has a large or small surface area or if the liquid is different (e.g., has a different density). It is important not to over-wet the powder to the point where it reaches a gel state, at which point the reaction product, when dried, will not be the same as the original. Over-wetting will also result in agglomerates and grit when dried.

[0031] When dried at low temperatures, 50°C to 120°C, the reaction product retains a hydration layer on the surface of the fumed silica. It is possible to further modify the surface of the silica (remove the hydration layer) by heat treatment at higher temperatures, i.e., 120°C to 1000°C. High temperatures are required to remove the hydration layer on the surface of the silica. How high the temperature is depends on the level of drying required.

[0032] It should be understood that the present invention is not limited to densified materials that have not been subjected to various other densification processes, for example, fumed silica that has previously been partially densified by mechanical or other means is also within the scope of the present invention.

[0033] The low density bulk material is mixed with the liquid for a time effective to reduce the volume of the low bulk density material, and then the liquid is removed from the mixture. Typically, the removal of the liquid from the mixture will be accomplished by evaporation. However, depending on the particular bulk density material and liquid, it is preferred to carry out the evaporation of the liquid using a rotary dryer, freeze dryer, fluidized bed dryer, spray dryer, or similar drying equipment known in the art of powder drying, at atmospheric or reduced pressure. Other methods for removing liquid from powders will be apparent to those skilled in the art. However, evaporation is the most preferred means for removing the liquid.

[0034] The time required to remove substantially all of the liquid from the powder will depend primarily on the liquid employed, its vapor pressure, and the batch size for preparation. Completion of the drying step can be easily determined by observing the powder being dried, or more conveniently, by simply allowing the drying to continue for an extended period of time. Obviously, the removal of liquid will be more rapid if the liquid has a low boiling temperature and the liquid / low bulk density mixture is vigorously stirred in the presence of a purge gas such as nitrogen. On the other hand, the process of the present invention proceeds more slowly when a high boiling liquid is used, the process temperature is relatively low, there is no purge gas, and the agitation of the filler / liquid mixture is minimal. The reaction product thus obtained (after drying) is a free-flowing powder containing only limited amounts of agglomerates, i.e., a homogeneous powder-like material with a bulk density much higher than that of the original fumed silica powder.

[0035] The densification of low bulk density materials in the present invention results in materials such as fumed silica that have substantially higher bulk densities, are free of unacceptable amounts of agglomerates and grit, and are easily mixed with other materials, such as silicone polymers used to make room temperature vulcanizable (RTV) compositions. The densified fumed silica materials can also be used as liquid carriers, "carried" with aqueous liquids, resulting in novel free-flowing reaction products containing the carried liquid.

[0036] Examples of aspects of the present invention As is apparent from the foregoing description, the present invention can be embodied and taken in a wide variety of forms. For example:

[0037] In an aspect 1, the present invention provides a method for increasing the bulk density of fumed silica, comprising the steps of: (A) adding a liquid via dripping or spraying to a low bulk density fumed silica material; (B) gently mixing the low bulk density material and the liquid for a time effective to reduce the volume of the original low bulk density material while preserving the homogeneity of the low bulk density material; and (C) removing substantially all of said liquid to obtain a material having an increased bulk density.

[0038] In embodiment 2, the liquid of the method of embodiment 1 is an aqueous solution.

[0039] In an embodiment 3, the liquid of the method of embodiment 1 or 2 is a polar liquid or a non-polar liquid.

[0040] In an embodiment 4, the liquid in the method of any one of embodiments 1 to 3 is water.

[0041] In an embodiment 5, the liquid of the method of any one of embodiments 1-4 is selected from the group consisting of aqueous solutions of acids, bases, alcohols, esters, ketones, salts, soluble polymers, surfactants, enzymes, and mixtures thereof.

[0042] In an embodiment 6, the liquid of the method of any one of the embodiments 1-5 further comprises a colorant, a flavorant, or a mixture thereof.

[0043] In an embodiment, the fumed silica of the method of any one of the embodiments 1-6 is hydrophilic, hydrophobic, or a mixture thereof.

[0044] In an embodiment, the aqueous liquid of the method of embodiment 1 is selected from the group consisting of hydrogen peroxide, peracetic acid, or a mixture thereof.

[0045] In embodiment 9, the method of embodiments 1-8, wherein in step (A), the liquid is added to the mixing vessel by a spraying method while gently mixing the low bulk density material, thereby maintaining the homogeneity of the low bulk density material.

[0046] In embodiment 10, the method of embodiments 1-9, wherein the low bulk density fumed silica has been partially densified beforehand.

[0047] In embodiment 11, the method of embodiment 10, wherein the partial densification is performed by mechanical means.

[0048] In an embodiment 12, the method of any one of the preceding embodiments, wherein substantially all of the aqueous liquid is removed by evaporation.

[0049] In some embodiments, the invention herein may be construed to exclude various elements and process steps that do not materially affect the basic and novel characteristics of the composition or the process for making the composition. Further, in some embodiments, the invention may be construed to exclude various elements and process steps not specified herein. EXAMPLES

[0050] Example 1: A total of 80 g of fumed silica was placed in an open tray. A total of 186.7 g of water containing acid (e.g., 85% phosphoric acid was added to the liquid to give a final concentration of 2% phosphoric acid in the liquid) was added dropwise under gentle stirring to ensure that all the liquid was adsorbed onto the powder. The weight ratio between solids and liquid was 30 / 70 (solids / liquid). Fumed silica (Cab-o-sil M5®): 80.0 g Water + phosphoric acid: 186.7g Total: 266.7g

[0051] The mixture (i.e., liquid-filled powder) was blended in a Waring Commercial mixer (Waring X-Prep - speed 6.5) with three short mixing breaks of 10 seconds each. Strong densification of the powder was observed during this process.

[0052] The powder was then placed in a tray and dried in an oven at 50°C (122°F) for several days. The powder so obtained was a free-flowing powder with a tap density of 0.284 g / mL. The original tap density of the fumed silica (Cab-o-sil® M5) was 50 g / L or 0.05 g / mL (untreated silica, Cab-o-sil® M5). This corresponds to a densification factor of 4.96. The final product was a densified, free-flowing fumed silica with phosphate. The tap density was measured using a graduated cylinder according to ASTM D7481-18: "Standard Test Methods for Determining Loose and Tapped Bulk Densities of Powders".

[0053] Example 2: The same composition as in Example 1 (80 g fumed silica + 186.7 g phosphoric acid in water, final concentration in liquid: 2% phosphoric acid) was made and blended in a Waring blender at high speed setting for 1 minute. The reaction product thus obtained was a saturated reaction product with a paste aspect, which formed a coarse granular reaction product upon drying.

[0054] Example 3: A total of 80 g of fumed silica was placed in an open tray. A total of 170 g of deionized water was added dropwise under gentle stirring to ensure that all the liquid was adsorbed onto the powder. The weight ratio between solids and liquid was 32 / 68 (solids / liquid). Fumed silica: 80.0g DI water: 170.0g Total: 250.0g

[0055] The mixture (i.e., liquid-filled powder) was blended in a commercial Waring mixer with three short mixing breaks of 10 seconds each. Strong densification of the powder was observed during this process.

[0056] The powder was then placed in a tray and dried in an oven at 50°C (122°F) for several days. The powder so obtained was a free-flowing powder with a tap density of 0.23 g / L (according to ASTM D7481-18). The original tap density of the fumed silica (Cab-o-sil® M5) was 0.05 g / L. Its densification factor was 4.6.

[0057] The final product was a densified, free-flowing fumed silica. The reaction product had the same composition as the original bulk powder, but with a hydrated surface and was free of impurities.

[0058] Example 4: The densified fumed silica obtained in Example 1 was treated with an aqueous liquid, a 12% solution of peracetic acid, where the aqueous liquid was absorbed by the densified fumed silica. The powder thus obtained was a free-flowing powder containing a peracetic acid formulation. Fumed silica (Cab-o-sil® M5): 80.0 g Peracetic acid 12% concentration (SaniDate® 12.0): 186.7 g Total: 266.7g

[0059] Pretreatment of the fumed silica with phosphoric acid according to the process described above did not change the absorption performance of the final densified fume silica compared to the reaction product made without densification treatment.

Claims

1. 1. A method for increasing the bulk density of fumed silica, comprising: (A) adding a liquid via dripping or spraying to a low bulk density fumed silica material; (B) gently mixing the low bulk density material and the liquid for a time effective to reduce the volume of the original low bulk density material while preserving the homogeneity of the low bulk density material; and (C) removing substantially all of the liquid to obtain a material having an increased bulk density; The method includes:

2. The method of claim 1 , wherein the liquid is an aqueous solution.

3. The method of claim 1 , wherein the liquid is a polar liquid or a non-polar liquid.

4. The method of claim 1 , wherein the liquid is water.

5. 10. The method of claim 1, wherein the liquid is selected from the group consisting of aqueous solutions of acids, bases, alcohols, esters, ketones, salts, soluble polymers, surfactants, enzymes, and mixtures thereof.

6. The method of claim 5 , wherein the liquid further comprises a colorant, a flavorant, or a mixture thereof.

7. The method of claim 1 , wherein the fumed silica is hydrophilic, hydrophobic, or a mixture thereof.

8. 10. The method of claim 1, wherein the aqueous liquid is selected from the group consisting of hydrogen peroxide, peracetic acid, or a mixture thereof.

9. 2. The method of claim 1, wherein in step (A), the liquid is added to the mixing vessel by a spraying method while gently mixing the low bulk density material, thereby maintaining homogeneity of the low bulk density material.

10. The method of claim 1 , wherein the low bulk density fumed silica has been previously partially densified.

11. The method of claim 10, wherein the partial densification is performed by mechanical means.

12. The method of claim 1 , wherein substantially all of the aqueous liquid is removed by evaporation.